Análisis de la agenda informativa del Noticiero estelar de “TVS” en la Opinión Pública de los Ciudadanos de Riobamba, periodo octubre 2017-marzo 2018 - Redín Palacios, Jocelyn Paola (2019)
This research entitled “"Analysis of the Informative Agenda of the Stellar Newscast of "TVS" in the Public Opinion of Riobamba Citizens, Period October 2017-March 2018 ", it was planted as an objective to carry out an analysis of the Informative Agenda of the Stellar Newscast of "TVS" and the impact that this generates in the opinion of the citizens. Being a field research and descriptive work, through the use of information collection tools that are applied in this research, data can be obtained little by little as they were generating ideas based on new communication strategies that is the proposal of this work, the tools used were surveys applied to the urban sector of Riobamba. In the analysis of the results, a lack of organized work in the communication department of the institution was identified, giving more importance to the dissemination of contents; also interviews where it was also announced the fundamentals of correct management of the Informative Agenda of the Stellar Newscast. The theoretical fundamentals that is applied through the analysis of books, articles, the website of the institution, as well as their social networks and traditional media.